MODEL KOOPERATIF TIPE PAIR CHECK DALAM PEMBELAJARAN MEMBACA UNTUK MENINGKATKAN KUALITAS LITERASI - Nurjanah Nurjanah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This paper is based on the results of class action research. The study aims to improve the ability to read scanning through a cooperative learning type pair check model on class VIII MTs. Masularul Ulum Pemulutan, Ogan Ilir. The action hypothesis in this study is "Cooperative type paired learning model can improve reading learning scanning of class VIII students of MTs. Masdarul Ulum Ogan Ilir ". Data collection is done by observation and tests. This research was conducted in two cycles which each cycle through four stages. Cycle data is collected through observation sheets and assessment sheets. The data obtained were then analyzed to find out whether there was an increase in learning outcomes achieved by students. After going beyond the first cycle, in the second cycle the teaching and learning process showed satisfactory results compared to the previous cycle. The results of reading scanning skills in cycle II have increased from the first cycle and have reached the expected average value. From the results of the reading scanning scanning cycle II, MTs students. Masdarul Ulum almost achieved learning completeness up to 84.38% and the average student learning outcomes reached 74.4.